Coated positive electrode active material, method for producing coated positive electrode active material, and all-solid-state battery
By forming a coated portion of the scandium lithium phosphate-based or lithium borate-based system on the surface of the positive electrode active material of the all-solid battery, the high resistance problem caused by the reaction of the positive electrode active material and the solid electrolyte is solved, and the internal resistance reduction and the circulation characteristics are improved.
Patent Information
- Application Number
- CN202111382763.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-01
- Filing Date
- 2021-11-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-11-22
AI Technical Summary
In an all-solid battery, the reaction of the positive electrode active material and the solid electrolyte leads to the formation of a high resistance layer, which increases the internal resistance of the battery.
By providing a coating portion containing a scandium phosphate-based compound or a lithium borate-based compound on the surface of the positive electrode active material, the reaction between the positive electrode active material and the solid electrolyte can be suppressed. The coating portion is formed by a sputtering method, and specifically includes sputtering using a lithium scandium phosphate-based precursor compound or a lithium borate-based precursor compound as a target.
It effectively inhibits the reaction between the positive electrode active substance and the solid electrolyte, reduces the internal resistance of the all-solid battery, and improves the circulation characteristics of the battery.
Smart Images

Figure CN114583168B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a coated positive electrode active material, a method for producing the coated positive electrode active material, and an all-solid-state battery. Background Art
[0002] All-solid-state batteries are batteries having a solid electrolyte layer between a positive electrode active material layer and a negative electrode active material layer, and have the advantage that safety devices can be easily simplified compared to liquid-based batteries having an electrolyte solution containing a flammable organic solvent.
[0003] Attempts to suppress the reaction between the positive electrode active material and the solid electrolyte are known. For example, Patent Document 1 discloses a non-aqueous electrolyte battery in which an intermediate layer is formed between the positive electrode layer and the solid electrolyte layer, and the intermediate layer contains a Li ion conductive oxide (LiNbO 3-α ).
[0004] In addition, Patent Document 2 describes a positive electrode for an all-solid secondary battery, which contains a surface-treated positive electrode active material, wherein the surface-treated positive electrode active material is obtained by coating at least a portion of the surface of the positive electrode active material with an oxide containing at least one element from Group 13 of the periodic table.
[0005] In addition, Patent Document 3 describes a positive electrode active material for an alkaline storage battery, wherein 1 to 30% of the surface area of solid solution particles containing nickel hydroxide as the main component is coated with oxide particles of at least one selected from yttrium, scandium or lanthanide elements, and the outer periphery is coated with cobalt oxide having an average valence of cobalt greater than 3.0.
[0006] Patent document 4 describes a non-sintered nickel electrode for alkaline storage batteries, which is composed of a coated inner layer and a coated outer layer, the coated inner layer is composed of cobalt or a cobalt compound that covers the substrate particles, and the coated outer layer is composed of yttrium, scandium or lanthanide elements or their compounds that cover the coated inner layer.
[0007] Prior art literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-086555
[0009] Patent Document 2: Japanese Patent Application Publication No. 2010-192373
[0010] Patent Document 3: Japanese Patent Application Publication No. 2002-298840
[0011] Patent Document 4: Japanese Patent Application Laid-Open No. 11-007950 Summary of the invention
[0012] When the positive electrode active material reacts with the solid electrolyte, a high resistance layer is generated at the interface between the two, increasing the internal resistance of the all-solid-state battery.
[0013] The present disclosure has been made in view of the above-mentioned situation, and a main object of the present disclosure is to provide a positive electrode active material capable of suppressing a reaction with a solid electrolyte.
[0014] The present disclosure provides a coated positive electrode active material comprising: a positive electrode active material and a coating portion that covers at least a portion of the surface of the positive electrode active material, wherein the coating portion contains a lithium scandium phosphate compound or a lithium borate compound.
[0015] According to the present disclosure, by providing a coating portion containing a lithium scandium phosphate compound or a lithium borate compound on the surface of a positive electrode active material, a coated positive electrode active material capable of suppressing a reaction with a solid electrolyte can be obtained.
[0016] In the above disclosure, the molar ratio of the Li, Sc and P in the scandium phosphate lithium compound may satisfy Li:Sc:P=3.00:2.19-5.00:1.99-2.57.
[0017] In the above disclosure, in the above-mentioned scandium lithium phosphate compound, the molar ratio of Li to Sc (Li / Sc) may be 0.60 or more.
[0018] In the above disclosure, the molar ratio of Li to B in the above lithium borate compound may satisfy Li:B=3.00:5.04-6.72.
[0019] In the above disclosure, in the above lithium borate-based compound, the molar ratio of Li to B (Li / B) may be 0.60 or less.
[0020] In addition, the present disclosure provides a method for manufacturing a coated positive electrode active material, wherein the coated positive electrode active material comprises: a positive electrode active material, and a coating portion covering at least a portion of the surface of the positive electrode active material. The manufacturing method comprises a preparation step and a coating portion forming step. The preparation step prepares the positive electrode active material, and the coating portion forming step forms the coating portion on the surface of the positive electrode active material by a sputtering method using a scandium phosphate-based precursor compound or a lithium borate-based precursor compound as a target.
[0021] According to the present disclosure, a coated positive electrode active material capable of suppressing reaction with a solid electrolyte can be obtained by adopting a sputtering method using a lithium scandium phosphate precursor compound or a lithium borate precursor compound as a target.
[0022] In the above disclosure, the above-mentioned lithium scandium phosphate precursor compound can be Li3Sc2(PO4)3.
[0023] In the above disclosure, the lithium borate precursor compound may be Li3B7O12 .
[0024] In addition, the present disclosure provides an all-solid-state battery having a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer, wherein the positive electrode active material layer contains the coated positive electrode active material.
[0025] According to the present disclosure, since the positive electrode active material layer contains the above-mentioned coated positive electrode active material, it is possible to obtain a fully solid-state battery in which the reaction between the coated positive electrode active material and the solid electrolyte is suppressed.
[0026] In the above disclosure, the positive electrode active material in the coated positive electrode active material may be an oxide active material, and the positive electrode active material layer may contain a sulfide solid electrolyte.
[0027] According to the present disclosure, there is an effect that a positive electrode active material capable of suppressing a reaction with a solid electrolyte can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view showing an example of the coated positive electrode active material in the present disclosure.
[0029] Figure 2 This is a schematic cross-sectional view illustrating an example of an all-solid-state battery in the present disclosure.
[0030] Figure 3 These are the evaluation results of the single cell resistance of Examples 1-1 to 1-3.
[0031] Figure 4 These are the evaluation results of the single cell resistance of Examples 2-1 to 2-3.
[0032] Figure 5 These are the evaluation results of the single cell resistance of Comparative Examples 1-1 to 1-3.
[0033] Figure 6 These are the measurement results of the discharge capacity after each cycle of Examples 1-1 to 1-3.
[0034] Figure 7 These are the measurement results of the discharge capacity after each cycle of Examples 2-1 to 2-3.
[0035] Figure 8 These are the measurement results of the discharge capacity after each cycle of Comparative Examples 1-1 to 1-3.
[0036] Description of Reference Numerals
[0037] 1…Positive electrode active material layer
[0038] 2...Covered part
[0039] 10…Coated positive electrode active material
[0040] 11…Positive electrode active material layer
[0041] 12…Negative electrode active material layer
[0042] 13…Solid electrolyte layer
[0043] 14…Positive electrode collector
[0044] 15…Negative electrode collector
[0045] 20…All-solid-state battery DETAILED DESCRIPTION
[0046] A. Coated positive electrode active material
[0047] Hereinafter, the coated positive electrode active material in the present disclosure will be described in detail. Figure 1 This is a schematic cross-sectional view showing an example of the coated positive electrode active material in the present disclosure. Figure 1 The coated positive electrode active material 10 shown comprises a positive electrode active material 1 and a coating portion 2 that covers at least a portion of the surface of the positive electrode active material 1 , and the coating portion 2 contains a lithium scandium phosphate compound or a lithium borate compound.
[0048] According to the present disclosure, by providing a coating containing a lithium scandium phosphate compound or a lithium borate compound on the surface of the positive electrode active material, a coated positive electrode active material capable of suppressing the reaction with the solid electrolyte can be obtained. Specifically, the lithium scandium phosphate compound or the lithium borate compound can suppress the reaction between the positive electrode active material and the solid electrolyte in the same way as the conventional lithium niobate (LiNbO3). In addition, the oxidation potential of the lithium scandium phosphate compound or the lithium borate compound is higher than that of the conventional lithium niobate (LiNbO3). Due to the high oxidation potential, the reaction between the coating and the solid electrolyte during charging can be suppressed. As a result, the degradation of the coating and the solid electrolyte can be suppressed. In addition, due to the high oxidation potential, the oxidative decomposition of the lithium scandium phosphate compound or the lithium borate compound during charging can be suppressed. As a result, the internal resistance is not easily increased over time, and the improvement of the cycle characteristics can be sought.
[0049] 1. Covered part
[0050] The coating portion in the present disclosure is formed so as to cover at least a portion of the surface of the positive electrode active material. In addition, the coating portion contains a lithium scandium phosphate compound or a lithium borate compound.
[0051] The scandium phosphate lithium compound generally contains Li, Sc and PO4. In addition, the molar ratio of Li, Sc and P in the scandium phosphate lithium compound is not particularly limited, and for example, preferably satisfies Li:Sc:P=3.00:2.19-5.00:1.99-2.57. In addition, the scandium phosphate lithium compound preferably contains, for example, Li x Sc y (PO4) z The composition represented by x, y, and z preferably satisfy x:y:z=3.00:2.19-5.00:1.99-2.57.
[0052] In addition, in the scandium phosphate lithium compound, the molar ratio of Li to Sc is set to Li / Sc, the molar ratio of Li to P is set to Li / P, and the molar ratio of Sc to P is set to Sc / P. Li / Si is, for example, greater than 0.60, may be greater than 0.63, or may be greater than 0.80. On the other hand, Li / Sc is, for example, less than 1.37. Li / P is, for example, less than 1.50, or may be less than 1.40. On the other hand, Li / P is, for example, greater than 1.17. Sc / P is, for example, less than 2.51, may be less than 2.38, or may be less than 2.00. On the other hand, Sc / P is, for example, greater than 0.85.
[0053] The lithium borate compound generally contains Li, B and O. The molar ratio of Li to B in the lithium borate compound is not particularly limited, but preferably satisfies Li:B=3.00:5.04 to 6.72. a B b O c The composition represented by a, b, and c preferably satisfy a:b:c=3.00:5.04-6.72:9.06-12.0.
[0054] In the lithium borate compound, the molar ratio of Li to B is Li / B. Li / B is, for example, 0.60 or less, 0.58 or less, or 0.50 or less. On the other hand, Li / B is, for example, 0.45 or more.
[0055] The coating portion preferably contains a lithium scandium phosphate compound or a lithium borate compound as a main body. The proportion of the lithium scandium phosphate compound or the lithium borate compound in the coating portion is, for example, 50% by weight or more, 70% by weight or more, or 90% by weight or more. In addition, the coating portion may contain only a lithium scandium phosphate compound or only a lithium borate compound. In addition, the coating portion contains at least a lithium scandium phosphate compound or a lithium borate compound, and may also contain both a lithium scandium phosphate compound and a lithium borate compound.
[0056] The thickness of the coating portion is, for example, more than 5 nm, or more than 10 nm. On the other hand, the thickness of the coating portion is, for example, less than 100 nm, less than 50 nm, or less than 20 nm. If the coating portion is too thin, the effect of the present disclosure may not be obtained, and if the coating portion is too thick, the internal resistance of the all-solid-state battery may increase. For example, the thickness of the coating portion can be measured using a transmission electron microscope (TEM) or the like.
[0057] The coating portion covers at least a portion of the surface of the positive electrode active material. The coating portion may be formed on a portion of the surface of the positive electrode active material, or may be formed on the entire surface. The coverage of the coating portion may be, for example, 50% or more, 70% or more, or 90% or more. On the other hand, the coverage of the coating portion may be 100% or less than 100%. The coverage may be determined by X-ray photoelectron spectroscopy (XPS). Furthermore, the positive electrode active material and the coating portion may be in direct contact or may be arranged with other layers interposed therebetween.
[0058] The method for forming the coating portion is described in detail in “B. Method for producing coated positive electrode active material” to be described later, and therefore description thereof is omitted here.
[0059] 2. Positive electrode active material
[0060] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials, LiMn2O4, LiNi 0.5 Mn 1.5 O4 and other spinel active materials, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 and other olivine active materials. In particular, when the positive electrode active material is an oxide active material and the positive electrode active material layer contains a sulfide solid electrolyte, a high resistance layer is easily formed at the interface between the oxide active material and the sulfide solid electrolyte. Even in this case, the reaction between the oxide active material and the sulfide solid electrolyte can be suppressed by providing the above-mentioned coating portion.
[0061] The shape of the positive electrode active material may be, for example, a granular shape. The average particle size (D 50 ) is not particularly limited, and may be, for example, 10 nm or more, or 100 nm or more. On the other hand, the average particle size (D 50 ) is, for example, 50 μm or less, or 20 μm or less. 50) can be calculated, for example, by measurement using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM).
[0062] 3. Coated positive electrode active material
[0063] The active material in the present disclosure is generally used in all-solid batteries. All-solid batteries are described in detail in "C. All-solid batteries" described later, so description here is omitted.
[0064] B. Method for producing coated positive electrode active material
[0065] In the manufacturing method of the coated positive electrode active material disclosed in the present invention, the above-mentioned coated positive electrode active material has a positive electrode active material and a coating part that covers at least a portion of the surface of the above-mentioned positive electrode active material. The above-mentioned manufacturing method has a preparation step and a coating part forming step. The above-mentioned preparation step prepares the above-mentioned positive electrode active material, and the above-mentioned coating part forming step adopts a sputtering method using a lithium scandium phosphate precursor compound or a lithium borate precursor compound as a target to form the above-mentioned coating part on the surface of the above-mentioned positive electrode active material.
[0066] According to the present disclosure, a coated positive electrode active material capable of suppressing reaction with a solid electrolyte can be obtained by adopting a sputtering method using a lithium scandium phosphate precursor compound or a lithium borate precursor compound as a target.
[0067] The preparation step in the present disclosure is a step of preparing a positive electrode active material. The positive electrode active material can be prepared by synthesizing it by itself or by purchasing a commercial product. Regarding the positive electrode active material, it is the same as "A. Coated positive electrode active material", so the description here is omitted.
[0068] The coating forming step in the present disclosure is a step of forming the coating on the surface of the positive electrode active material by sputtering using a lithium scandium phosphate precursor compound or a lithium borate precursor compound as a target.
[0069] Scandium phosphate lithium precursor compounds generally contain Li, Sc, and PO4. Examples of scandium phosphate lithium precursor compounds include Li3Sc2(PO4)3. On the other hand, lithium borate precursor compounds include Li, B, and O. Examples of lithium borate precursor compounds include Li3B7O 12 As the sputtering method, for example, drum sputtering is preferred because it can form a film uniformly on the surface of the positive electrode active material. The thickness of the coating portion can be adjusted by adjusting the sputtering time, etc.
[0070] In the coating forming step, heat treatment may or may not be performed after the above-mentioned sputtering, but the latter is preferred. Because this can further suppress the reaction with the solid electrolyte. On the other hand, in the former case, the heat treatment temperature is, for example, 300°C or more, or 400°C or more. As the heat treatment atmosphere, for example, an argon atmosphere can be cited. In addition, the heat treatment time is, for example, 1 hour or more and 10 hours or less, preferably about 5 hours.
[0071] C. All-solid-state battery
[0072] Figure 2 This is a schematic cross-sectional view of the all-solid-state battery disclosed herein. Figure 2 The all-solid-state battery 20 shown has: a positive electrode active material layer 11 containing the above-mentioned coated positive electrode active material, a negative electrode active material layer 12, a solid electrolyte layer 13 formed between the positive electrode active material layer 11 and the negative electrode active material layer 12, a positive electrode collector 14 for collecting current from the positive electrode active material layer 11, and a negative electrode collector 15 for collecting current from the negative electrode active material layer 12.
[0073] According to the present disclosure, since the positive electrode active material layer contains the above-mentioned coated positive electrode active material, it is possible to obtain an all-solid-state battery in which the reaction between the coated positive electrode active material and the solid electrolyte is suppressed.
[0074] 1. Positive electrode active material layer
[0075] The positive electrode active material layer is a layer containing at least the above-mentioned coated positive electrode active material, and may also have at least one of a solid electrolyte, a conductive material and a binder as needed. The content of the coated positive electrode active material in the positive electrode active material layer is not particularly limited, and can be appropriately determined according to the performance of the target battery. The proportion of the coated positive electrode active material in the positive electrode active material layer is, for example, more than 20% by weight, more than 30% by weight, or more than 40% by weight. On the other hand, the proportion of the coated positive electrode active material is, for example, less than 80% by weight, less than 70% by weight, or less than 60% by weight.
[0076] The positive electrode active material layer preferably contains a solid electrolyte. The solid electrolyte may be a conventionally known solid electrolyte commonly used in all-solid lithium ion batteries, for example, a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, a halide solid electrolyte, etc., among which a sulfide solid electrolyte is preferred. In particular, in the positive electrode active material layer, the sulfide solid electrolyte is preferably in contact with the coated positive electrode active material. This is because the effect of the present disclosure can be better enjoyed.
[0077] Examples of the sulfide solid electrolyte include a solid electrolyte containing Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S element. In addition, the sulfide solid electrolyte may further contain at least one of O element and halogen element. Examples of the halogen element include F element, Cl element, Br element, and I element.
[0078] The sulfide solid electrolyte preferably has an anion structure of the original composition (PS4 3- Structure, SiS4 4- Structure, GeS4 4- Structure, AlS3 3- Structure, BS3 3- Structure) as the main component of the anion. Because of its high chemical stability. Relative to all the anion structures in the sulfide solid electrolyte, the proportion of the anion structure of the original composition is, for example, 70 mol% or more, and can also be 90 mol% or more. The proportion of the anion structure of the original composition can be determined, for example, by Raman spectroscopy, NMR, and XPS. Specific examples of sulfide solid electrolytes include xLi2S·(100-x)P2S5(70≤x≤80), yLiI·zLiBr·(100-yz)Li3PS4(0≤y≤30, 0≤z≤30).
[0079] The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte or a glass-ceramic sulfide solid electrolyte. The glass-based sulfide solid electrolyte may be obtained by vitrifying the raw material. The glass-ceramic sulfide solid electrolyte may be obtained, for example, by heat treating the glass-based sulfide solid electrolyte. In addition, the sulfide solid electrolyte preferably has a predetermined crystal structure. Examples of the crystal structure include a Thio-LISICON type crystal structure, an LGPS type crystal structure, and an Argyrodite type crystal structure.
[0080] The shape of the solid electrolyte may be, for example, a granular shape. The average particle size of the solid electrolyte may be, for example, 0.05 μm or more, or 0.1 μm or more. On the other hand, the average particle size of the solid electrolyte may be, for example, 50 μm or less, or 20 μm or less. The average particle size of the solid electrolyte may be defined as D 50 , can be calculated by, for example, measurement using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM).
[0081] The positive electrode active material layer may contain a conductive material. By using a conductive material, the electronic conductivity in the positive electrode active material layer can be improved. As the conductive material, for example, carbon materials, metal particles, and conductive polymers can be cited. As the carbon material, for example, granular carbon materials such as acetylene black (AB) and Ketjen black (KB), carbon fibers, carbon nanotubes (CNT), fibrous carbon materials such as carbon nanofibers (CNF) can be cited.
[0082] In addition, the positive electrode active material layer may contain a binder. By using a binder, the compactness of the positive electrode active material layer can be improved. As a binder, for example, rubber-based binders such as butadiene rubber (BR) and styrene butadiene rubber (SBR), fluorine-based binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE) can be cited. The thickness of the positive electrode active material layer is, for example, greater than 0.1 μm and less than 1000 μm. As a method for forming a positive electrode active material layer, for example, a method of applying a mixture containing at least a coated positive electrode active material and a dispersion medium and drying it can be cited.
[0083] 2. Negative electrode active material layer
[0084] The negative electrode active material layer is a layer containing at least a negative electrode active material. In addition, the negative electrode active material layer may also contain at least one of a solid electrolyte, a conductive material, and a binder as required.
[0085] The negative electrode active material is not particularly limited, and examples thereof include metal active materials, carbon active materials, and oxide active materials. Examples of the metal active material include metal simple substances and metal alloys. Examples of the metal elements contained in the metal active material include Si, Sn, In, and Al. The metal alloy is preferably an alloy containing the above metal elements as main components.
[0086] On the other hand, examples of carbon active materials include mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. In addition, examples of oxide active materials include Li4Ti5O 12 Lithium titanate etc.
[0087] The proportion of the negative electrode active material in the negative electrode active material layer is, for example, 20% by weight or more, 30% by weight or more, or 40% by weight or more. On the other hand, the proportion of the negative electrode active material is, for example, 80% by weight or less, 70% by weight or less, or 60% by weight or less.
[0088] The solid electrolyte, the conductive material, and the binder are the same as those described in the above-mentioned “1. Positive electrode active material layer”, and thus are omitted here. The thickness of the negative electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.
[0089] 3. Solid electrolyte layer
[0090] The solid electrolyte layer is a layer formed between the positive electrode active material layer and the negative electrode active material layer, and contains at least a solid electrolyte. In addition, the solid electrolyte layer may contain only a solid electrolyte, or may further contain a binder.
[0091] The solid electrolyte layer preferably contains a sulfide solid electrolyte as a solid electrolyte. In particular, the sulfide solid electrolyte contained in the solid electrolyte layer is preferably in contact with the coated positive electrode active material contained in the positive electrode active material layer. Regarding the sulfide solid electrolyte and the binder, the contents described in the above "1. Positive electrode active material layer" are the same, so the description here is omitted. The thickness of the solid electrolyte layer is, for example, not less than 0.1 μm and not more than 1000 μm.
[0092] 4. Others
[0093] The all-solid battery in the present disclosure preferably has a positive electrode current collector for collecting the positive electrode active material layer, and a negative electrode current collector for collecting the negative electrode active material layer. As the material of the positive electrode current collector, for example, SUS, aluminum, nickel, iron, titanium and carbon can be cited. On the other hand, as the material of the negative electrode current collector, for example, SUS, copper, nickel and carbon can be cited.
[0094] The type of all-solid-state battery in the present disclosure is not particularly limited, and a typical example is a lithium-ion battery. In addition, the battery in the present disclosure may be a primary battery or a secondary battery, and a secondary battery is preferred. Because it can be repeatedly charged and discharged, it is useful as, for example, a vehicle-mounted battery.
[0095] The all-solid battery in the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a stacked battery in parallel) or a bipolar stacked battery (a stacked battery in series). Examples of the shape of the battery include a coin-shaped, laminated, cylindrical, and square shape.
[0096] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and all schemes having substantially the same technical ideas as those described in the scope of the claims of the present disclosure and having the same functions and effects are included in the technical scope of the present disclosure.
[0097] [Example]
[0098] Hereinafter, the all-solid-state battery of the present disclosure will be described in more detail using Examples and Comparative Examples.
[0099] [Example 1-1]
[0100] (Fabrication of Positive Electrode Active Material Layer)
[0101] For 10g of NCM (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, positive electrode active material), and coated by roller sputtering using a target of Li3Sc2(PO4)3. Thus, a coated positive electrode active material having a coating portion with a thickness of 10 nm was obtained.
[0102] Add PVDF, the coated positive electrode active material obtained above, solid electrolyte (Li2S-P2S5 glass ceramic) and conductive material (vapor-grown carbon fiber, VGCF, manufactured by Showa Denko) to a polypropylene (PP) container, and stir the PP container for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT). Next, vibrate the PP container for 3 minutes using a vibrator (TTM-1 manufactured by Shibata Science), and stir it for 30 seconds using an ultrasonic dispersion device to obtain a coating liquid. Use an applicator to apply the obtained coating liquid to an Al foil (manufactured by Nippon Foil) substrate using a scraper method. After the coating layer is dried naturally, dry it on a hot plate at 100°C for 30 minutes to form a positive electrode active material layer on one surface of the Al foil substrate.
[0103] (Fabrication of Positive Electrode Collector)
[0104] Carbon black and PVDF-based binder (manufactured by Kureha) were weighed to a weight ratio of 30:70, and an organic solvent was added to obtain a coating liquid. The coating liquid was applied to an Al foil (thickness: 15 μm) using an applicator by a doctor blade method, and dried naturally, and then dried on a hot plate at 100° C. for 30 minutes. Thus, a positive electrode current collector having a carbon layer with a thickness of 2 μm on one surface of the Al foil was formed.
[0105] (Production of negative electrode)
[0106] Add a PVDF-based binder (manufactured by Kureha), a negative electrode active material (lithium titanate (LTO)) and the above-mentioned solid electrolyte to a PP container, and stir the PP container for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT) to obtain a coating liquid. Next, prepare a Cu foil (negative electrode collector), and use an applicator to apply the obtained coating liquid by a doctor blade method. After allowing the coated electrode to dry naturally, dry it on a heating plate at 100°C for 30 minutes. Thus, a negative electrode active material layer is formed on one surface of the Cu foil (negative electrode collector). Then, the same treatment is performed to form a negative electrode active material layer on the other surface of the Cu foil (negative electrode collector) to obtain a negative electrode.
[0107] (Fabrication of Solid Electrolyte Layer)
[0108] Add butyl butyrate and the above-mentioned solid electrolyte to a PP container, and stir the PP container for 30 seconds with an ultrasonic dispersion device (UH-50 made by SMT). Next, vibrate the PP container for 30 minutes with a vibrator (TTM-1 made by Shibata Science), and stir it for 30 seconds with an ultrasonic dispersion device to obtain a coating liquid. Use an applicator to apply the obtained coating liquid to an Al foil (made by Nippon Foil) substrate by a doctor blade method, dry it naturally, and dry it on a hot plate at 100°C for 30 minutes to obtain a transfer member having an Al foil and a solid electrolyte layer.
[0109] The two obtained transfer members are respectively arranged on the negative electrode active material layer formed on both sides of the negative electrode collector for pressing, and the Al foil substrate of the transfer member is peeled off. Thus, a solid electrolyte layer is formed on the negative electrode active material layer. The obtained laminate is punched into a size larger than the positive electrode collector obtained above. Next, the two obtained positive electrode active material layers are respectively arranged on the solid electrolyte layer formed on both sides of the negative electrode for pressing, and the Al foil substrate formed with the positive electrode active material layer is peeled off from the positive electrode active material layer and pressed. Thus, an electrode laminate having a negative electrode active material layer, a solid electrolyte layer and a positive electrode active material layer on both sides of the negative electrode collector is obtained.
[0110] Next, the positive electrode collector is attached to both sides of the obtained electrode stack using an adhesive. Thus, a fully solid battery having a two-layer stacked unit structure with positive electrode collectors formed on both sides of the above-mentioned electrode stack is obtained. At this time, the carbon layer side of the positive electrode collector is configured to contact the positive electrode active material layer of the electrode stack. Furthermore, a plurality of the obtained two-layer stacked unit structures are stacked, and after terminal welding, they are sealed with a laminate film to obtain a battery for evaluation.
[0111] [Example 1-2]
[0112] A coated positive electrode active material was obtained in the same manner as in Example 1-1 except that the coated positive electrode active material was heat treated in an Ar atmosphere at 300° C. for 5 hours after barrel sputtering. An evaluation battery was obtained in the same manner as in Example 1-1 except that the coated positive electrode active material was used.
[0113] [Examples 1-3]
[0114] A coated positive electrode active material was obtained in the same manner as in Example 1-1 except that the coated positive electrode active material was heat treated in an Ar atmosphere at 400° C. for 5 hours after barrel sputtering. An evaluation battery was obtained in the same manner as in Example 1-1 except that the coated positive electrode active material was used.
[0115] [Example 2-1]
[0116] Using Li3B7O 12A coated positive electrode active material was obtained in the same manner as in Example 1-1 except that the target was used. A battery for evaluation was obtained in the same manner as in Example 1-1 except that the obtained coated positive electrode active material was used.
[0117] [Example 2-2]
[0118] A coated positive electrode active material was obtained in the same manner as in Example 2-1 except that the coated positive electrode active material was heat treated in an Ar atmosphere at 300° C. for 5 hours after barrel sputtering. An evaluation battery was obtained in the same manner as in Example 2-1 except that the coated positive electrode active material was used.
[0119] [Example 2-3]
[0120] A coated positive electrode active material was obtained in the same manner as in Example 2-1 except that the coated positive electrode active material was heat treated in an Ar atmosphere at 400° C. for 5 hours after barrel sputtering. An evaluation battery was obtained in the same manner as in Example 2-1 except that the coated positive electrode active material was used.
[0121] [Comparative Example 1-1]
[0122] A coated positive electrode active material was obtained in the same manner as in Example 1-1 except that LiNbO 3 was used as a target. A battery for evaluation was obtained in the same manner as in Example 1-1 except that the obtained coated positive electrode active material was used.
[0123] [Comparative Example 1-2]
[0124] A coated positive electrode active material was obtained in the same manner as in Comparative Example 1-1 except that the coated positive electrode active material was heat treated in an Ar atmosphere at 300° C. for 5 hours after barrel sputtering. An evaluation battery was obtained in the same manner as in Comparative Example 1-1 except that the coated positive electrode active material was used.
[0125] [Comparative Examples 1-3]
[0126] A coated positive electrode active material was obtained in the same manner as in Comparative Example 1-1 except that the coated positive electrode active material was heat treated in an Ar atmosphere at 400° C. for 5 hours after barrel sputtering. An evaluation battery was obtained in the same manner as in Comparative Example 1-1 except that the coated positive electrode active material was used.
[0127] [Composition Analysis]
[0128] In order to determine the composition of the coating portion of the coated positive electrode active material produced in Example 1-1, Example 2-1 and Comparative Example 1-1, Li3Sc2(PO4)3, Li3B7O 12After forming a film on Al foil with a sputtering target of LiNbO3 for 24 hours, the composition of the coating portion was determined by ICP measurement.
[0129] In order to determine the composition of the coated portion of the coated positive electrode active material formed in Examples 1-2 and 2-2, Li3Sc2(PO4)3, Li3B7O 12 After forming a film on Al foil for 24 hours using a sputtering target of , a heat treatment was performed at 300° C. for 5 hours in an Ar atmosphere, and the composition of the coating portion was determined by ICP measurement.
[0130] In order to determine the composition of the coated portion of the coated positive electrode active material formed in Examples 1-3 and 2-3, Li3Sc2(PO4)3, Li3B7O 12 After forming a film on Al foil for 24 hours using a sputtering target of , a heat treatment was performed at 400° C. for 5 hours in an Ar atmosphere, and the composition of the coating portion was determined by ICP measurement.
[0131] The composition analysis results of Examples 1-1 to 1-3 and Examples 2-1 to 2-3 are shown in Tables 1 and 2. In addition, the composition analysis result of Comparative Example 1-1 was Li:Nb=1:0.99.
[0132] Table 1
[0133] Li Sc P Example 1-1 3.00 2.19 2.57 Example 1-2 3.00 5.00 1.99 Examples 1-3 3.00 4.74 1.99
[0134] Table 2
[0135] Li B Example 2-1 3.00 6.72 Example 2-2 3.00 5.13 Example 2-3 3.00 5.04
[0136] [Evaluation of cell resistance]
[0137] The cell resistance of the evaluation battery obtained above was measured. The measurement was carried out in the range of 1.5 to 3.0 V, after constant current-constant voltage charging at 0.33C at 25°C, constant current-constant voltage discharge to SOC40%, and discharge at a rate of 3C for 5 seconds, and the resistance was calculated based on the voltage drop (ΔV) at this time. Furthermore, the resistance obtained from the voltage drop during discharge to 0 to 0.1 seconds was determined as the reaction resistance, and the resistance obtained from the voltage drop during discharge to 0.1 to 5 seconds was determined as the diffusion resistance. The charge and discharge were repeated for 1 to 10 cycles with constant current charging and constant current discharging at 0.33C as one cycle, and the resistance of the all-solid-state battery after each cycle was measured. The result of SOC40% is shown in Figure 3 to Figure 5 and Table 3.
[0138] Table 3
[0139]
[0140] ※The unit of resistance is Ωcm 2
[0141] like Figure 3 to Figure 5 As shown in Table 3, it was confirmed that Examples 1-1 to 1-3 and Examples 2-1 to 2-3 had the same internal resistance as Comparative Examples 1-1 to 1-3. Furthermore, although the internal resistance of Comparative Example 1-3 was lower, as described later, good evaluation was not obtained in the cycle characteristics. It is speculated that the reason is that oxygen deficiency occurs in the formed coating, thereby generating electronic conductivity, and oxidative decomposition of the solid electrolyte occurs at the interface between the positive electrode active material and the solid electrolyte. In addition, as Figure 3 As shown, by comparing Examples 1-1 to 1-3, it was confirmed that the higher the heat treatment temperature, the more the internal resistance in each cycle tended to increase. It is speculated that this is because the heat treatment caused Li and P defects, which affected the conductivity and oxidation resistance of the coating. In addition, in Examples 1-1 to 1-3, it was confirmed that the internal resistance tended to increase as the number of cycles increased. In addition, as Figure 4 As shown, in Examples 2-1 to 2-3, the same tendency as that of Examples 1-1 to 1-3 was confirmed.
[0142] [Cycle characteristics evaluation]
[0143] The above-obtained evaluation battery was subjected to the above-mentioned charge-discharge cycle 50 times, and the measurement results of the discharge capacity after each cycle are shown in FIG. Figure 6 to Figure 8 .
[0144] like Figure 6 As shown, the cycle characteristics obtained good results in the order of Example 1-1, Example 1-2, and Example 1-3. Figure 3 As shown in the figure, the internal resistance decreases in the order of Example 1-1, Example 1-2, and Example 1-3, so it is suggested that the lower the internal resistance, the better the cycle characteristics. Figure 7 As shown, the cycle characteristics obtained good results in the order of Example 2-1, Example 2-2, and Example 2-3. Figure 4 As shown in the figure, the internal resistance decreases in the order of Example 2-1, Example 2-2, and Example 2-3, so it is suggested that the lower the internal resistance, the better the cycle characteristics. Figure 8 As shown, the cycle characteristics obtained good results in the order of Comparative Example 1-1, Comparative Example 1-2, and Comparative Example 1-3, but the cycle characteristics were significantly reduced in Comparative Example 1-3.
Claims
1. An all-solid-state battery comprising a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer, The positive electrode active material layer contains a coated positive electrode active material. The coated positive electrode active material comprises a positive electrode active material and a coating portion that covers at least a portion of the surface of the positive electrode active material. The coating portion contains a scandium phosphate lithium compound, The molar ratio of Li, Sc and P in the lithium scandium phosphate compound satisfies Li:Sc:P=3.00:2.19~5.00:1.99~2.57, In the lithium scandium phosphate compound, a molar ratio of Li to Sc, i.e., Li / Sc, is 0.80 or more and 1.37 or less, and a molar ratio of Sc to P, i.e., Sc / P, is 2.00 or less, The coated positive electrode active material is manufactured by adopting a sputtering method using a lithium scandium phosphate precursor compound as a target to form the coating portion on the surface of the positive electrode active material, and not performing heat treatment after sputtering. The lithium scandium phosphate precursor compound is Li3Sc2(PO4)3.
2. The all-solid-state battery according to claim 1, The positive electrode active material in the coated positive electrode active material is an oxide active material, The positive electrode active material layer contains a sulfide solid electrolyte.
3. A method for producing a coated positive electrode active material, the coated positive electrode active material comprising: a positive electrode active material, and a coating portion coating at least a portion of a surface of the positive electrode active material, The manufacturing method comprises a preparation step and a coating forming step. The preparation step prepares the positive electrode active material. The coating forming step adopts a sputtering method using a scandium phosphate lithium precursor compound as a target to form the coating on the surface of the positive electrode active material, and no heat treatment is performed after sputtering. The lithium scandium phosphate precursor compound is Li3Sc2(PO4)3, The coating portion contains a lithium scandium phosphate compound, and a molar ratio of Li, Sc, and P in the lithium scandium phosphate compound satisfies Li:Sc:P=3.00:2.19~5.00:1.99~2.57.
Citation Information
Patent Citations
Non-sintered nickel electrode for alkali storage battery
JP1999007950A
Positive electrode active material for alkaline storage battery, and the alkaline storage battery using the same
JP2002298840A
All-solid secondary battery
JP2010192373A
Nonaqueous electrolyte battery, and manufacturing method thereof
JP2011086555A
Cathode active material for lithium battery, lithium battery, and method for producing cathode active material for lithium battery
CN105470475A